Validação de modelo de diabetes tipo 2 em camundongos, identificação de componentes bioativos e investigação dos efeitos anti-hiperglicemiantes, antidiabéticos e antioxidantes da polpa de Acrocomia aculeata em modelo experimental in vivo - Dourado, Thainara Agnis (2024)
Hronic non-communicable diseases, such as cardiovascular diseases, cancer, diabetes mellitus (DM) and chronic respiratory diseases, have generated an excessive number of premature deaths, loss of quality of life and negative economic impacts on society in general. One way of reducing the impact of chronic non-communicable diseases is to use functional foods. The inclusion of these foods in the diet can significantly contribute to better metabolic control, maintenance of body composition and individual immunity. Acrocomia aculeata (Jacq.) Lodd. ex Mart., popularly known as macaúba or bocaiuva, can be found throughout much of Brazil, and is abundant in the Midwest region, especially in Mato Grosso and Mato Grosso do Sul. Various studies have shown the antidiabetic, anti-inflammatory, antioxidant and diuretic activities of the oil from the pulp of A. aculeata. In view of this, our proposal was to validate a model of DM2 in mice and verify whether the consumption of A. aculeata pulp influences the modulation of food intake due to the high fiber content, associated with the presence of phenolic compounds in the pulp, and thus lead to an improvement in metabolic parameters, such as glycemic control, thus preventing the appearance of comorbidities associated with DM2. Analysis of the results revealed discrepancies in relation to the classic model of DM2, such as an increase in body mass over the period, a reduction in water intake and lower serum urea levels. The fact that the classic DM2 model was not exactly reproduced highlights the need to consider this model as an experimental representation of glucose intolerance, hypercholesterolemia and oxidative stress. And that the high gallic acid content observed in the fruit pulp was not enough to improve the glycemic parameters observed in animals with glucose intolerance. We believe that regular consumption of high doses of A. aculeata in its fresh form may induce insulin resistance.